Otimização dos processos de separação em hidrociclones filtrantes - Vieira, Luiz Gustavo Martins (2006)
Filtering Hydrocyclones are devices used to solid-liquid separation and they have porous cones. Thus, during the operation these devices, besides the traditional streams (underflow and overflow), there is still an additional liquid stream from the filtration on conical area. The study and optimization of the filtering hydrocyclones were proposed in this work to understand the influence of the filtration on the solid-liquid separation. Therefore, an experimental design was made and the main dimensions of a hydrocyclone were adopted, just like the inlet diameter, overflow diameter, total length and the angle of the cone. Moreover, computational fluid dynamics techniques (CFD) were subsidiary applied and conjugated to empirical data for understanding the filtering hydrocyclone performances. In according with the simulation and experimental data obtained in this study, on the used conditions, the filtration changed the flow inside hydrocyclone and it was a positive phenomenon on the filtering hydrocyclone performance because there was diminution on the energy cost and increase on the grade efficiency on the underflow stream.